Lymphotoxin α induces apoptosis, necroptosis and inflammatory signals with the same potency as tumour necrosis factor. (2nd August 2013) - Etemadi, Nima; Holien, Jessica K.; Chau, Diep; Dewson, Grant; Murphy, James M.; Alexander, Warren S.; Parker, Michael W.; Silke, John; Nachbur, Ueli
<x xml:space="preserve">Abstract</x> Both of the TNF superfamily ligands, TNF and LTα, can bind and signal through TNFR1 and TNFR2, yet mice mutant for each have different phenotypes. Part of this difference is because LTα but not TNF can activate Herpes Virus Entry Mediator and also heterotrimerise with LTβ to activate LTβR, which is consistent with the similar phenotypes of the LTα and LTβR deficient mice. However, it has also been reported that the LTα3 homotrimer signals differently than TNF through TNFR1, and has unique roles in initiation and exacerbation of some inflammatory diseases. Our modeling of the TNF/TNFR1 interface compared to the LTα3/TNFR1 structure revealed some differences that could affect signalling by the two ligands. To determine whether there were any functional differences in the ability of TNF and LTα3 to induce TNFR1‐dependent apoptosis or necroptosis, and if there were different requirements for cIAPs and Sharpin to transmit the TNFR1 signal, we compared the ability of cells to respond to TNF and LTα3. Contrary to our hypothesis, we were unable to discover differences in signalling by TNFR1 in response to TNF and LTα3. Our results imply that the reasons for the conservation of LTα are most likely due either to differential regulation, the ability to signal through Herpes Virus Entry Mediator or the ability of LTα to form heterotrimers with LTβ. Structured digital abstract LT alpha physically interacts with RIPK1 and cIAP1 by tandem affinity purification (View interaction) TNF and TNF bind by blue native page (View interaction) LT alpha and LT alpha bind by blue native page (View interaction) TNF physically interacts with cIAP1 and RIPK1 by tandem affinity purification (View interaction)